STRUKTUR KEPEMILIKAN DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Artini, Luh Gede Sri; Puspaningsih, Ni Luh Anik (Jurnal Keuangan dan Perbankan, 2011)
The companys long-term goal was to maximize corporate value. Maximization of corporate value could berealized by using the aspect of corporate financial decisions and the amount of stock ownership by managementin the company. This study aimed to determine the effect of direct and indirect ownership structure and capitalstructure toward dividend policy and firm value. Ownership structure was measured by total percentage ofstock ownership by management, capital structure was measured with debt to equity ratio (DER), dividendpolicy was measured by dividend payout ratio (DPR) and the value of the firm measured by price to book value(PBV). Population research was all the firms in the manufacturing industries listed in Indonesia Stock Exchange(IDX) from 2006 until the year of 2009 namely 149 companies. Sampling conducted in the researchwas purposive sampling method. Based on the criteria obtained by purposive sampling, 15 companies wereeligible to be utilized as the research sample. The results of this research were the impact of ownership structurewas not significant on dividend policy, the ownership structure had a significant positive impact on corporatevalue, capital structure did not significantly effect on dividend policy, capital structure did not significantlyaffect the value companies, dividend policy had a significant positive impact on corporate value.